Guía de fiestas tradicionales de la parroquia La Victoria del cantón Pujili de la provincia de Cotopaxi - Gualán Puchaicela, Alba Cecilia (2021)
The present research project began with a situational diagnosis of the study area and was based on determining the traditional festivals of the La Victoria parish of the Pujilí canton of the Cotopaxi province; in order to diagnose, inventory and protect traditional festivals as intangible heritage of the parish, through methods such as inductive, ethnographic, and synthetic; and research techniques such as the interview, observation, files of the INPC sub-area four of festivities which contributed to the safeguarding of cultural wealth, embodied in a descriptive guide that strengthens the growth, cultural, economic and tourist of this parish; To fulfill this purpose in this way to be able to strengthen, three specific objectives were developed, which were carried out through the application of qualitative methodology, which allowed the collection of primary and secondary information. To determine the situational diagnosis of the area, it was done through the de facto analysis that relates to four areas that are: socio-cultural, economic, environmental and tourism, the same ones that contributed with positive results in the development of the research. An inventory of the traditional festivals was then prepared by applying the qualitative methodology and the INPC files, which implied the application of techniques such as: observation, interview and question guide that contributed in the development of the INPC study, with which was able to know the number of cultural manifestations that exist in the site, information that was obtained from the parish GAD and the Plan of Development and Territorial Ordering of the year 2014 (PDOT), in this way it was possible to determine that in La Victoria parish its main activity economic is pottery, agriculture and livestock that comprise 75%, while 15% are dedicated to public entities such as: leisure and recreation businesses, lodging and food. The parish has a total population of 3,016 inhabitants distributed in 9 neighborhoods and 3 communities. Once the INPC files were applied, 12 traditional festivals resulted, in which 1 civic festival, 10 religious festivals or ceremonies and 1 called other festive celebrations were reflected; cultural manifestations that are intangible